PENGARUH ELECTRONIC WORD OF MOUTH TERHADAP LOYALITAS KONSUMEN YANG DIMEDIASI OLEH BRAND IMAGE DAN TRUST - Fadhlurrahman, Muhammad Rafii’; Sunaryo, Sunaryo (Jurnal Manajemen Pemasaran dan Perilaku Konsumen, 2022)
One of the uses of internet media in business applications is electronic commerce (e-commerce) or often also called electronic commerce. One of most used e-commerce by the Indonesian people is Tokopedia. This study aims to determine the effect of electronic word of mouth on consumer loyalty mediated by brand image and trust in Tokopedia users. The type of research used in this research is explanatory research. This study uses 100 samples, the sample is Tokopedia users in Malang City. The sampling technique used is a non-probability sampling technique , namely purposive sampling. Data analysis technique using SmartPLS 3.3. The results of this study indicate that electronic word of mouth has a direct positive and significant effect on consumer loyalty, brand image, and trust. Brand image and trust have a direct positive and significant influence on consumer loyalty. Brand image and trust have a positive and significant indirect influence in moderating electronic word of mouth on consumer loyalty.